Entender la desigualdad urbana en Lima Metropolitana: historia, multidimensionalidad y pistas para combatirla - Rodriguez Rivero, Luis (2023)
In Lima, as in other large Latin American cities, the daily experience of its inhabitants is framed by relations of inequality that go beyond the great economic differences normalized in capitalist societies. Urban inequality is presented as a multidimensional phenomenon in which its main components and the way they interact with each other is not universal, but have been constructed and structured throughout the history of each society, following the specific characteristics of each urban center, so we can refer of an intersectional inequality. A review of the urban history of Lima is proposed, which seeks to demonstrate how urban inequality has been constructed, and to show how the production of the city and the production of inequality have been two sides of the same process. Inequality and its relationship with fragmentation will be characterized, and then a conceptual model will be tested in accordance with the multidimensional nature of both. Finally, some clues to confront this analytical approach in a city like Lima will be pointed out.